PENGARUH KONTEN MARKETING TERHADAP CUSTOMER ENGAGEMENT ( Instagram Online Shop Produk Tas Segmen Middle Brand “@Shopashopishop” ) - Dexi Triadinda; Dini Yani (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2021)
The bag industry in the middle brand segment is currently being favored by most women. The growing industry in the digital era 4.0 has an impact on the way entrepreneurs market their products. By utilizing social media as a tool in promoting products, one of them is by sharing interesting content through Instagram. This study aims to analyze the effect of content marketing on customer engagement on Instagram accounts that sell @Shopashopishop_authentic middle brand bags. This research was carried out by distributing questionnaires to 96 respondents, namely followers of the Instagram account @Shopashopishop via Instagram direct messages. The research method used is quantitative with Simple Linear Regression Analysis Techniques. The results of the study indicate that content marketing has a significant influence on customer engagement. The influence of the independent variable of marketing content on the dependent variable of customer engagement is 73.3%